Trinity's children - Bara, Dave (Baen, 2022)
"Jared Clement has returned to Trinity, not as a mere ship captain but now as a 5 Suns Fleet Admiral. With his promotion comes increased responsibility that weighs heavy on his shoulders. 30,000 settlers are leaving the dying planets of the Rim, his home, and resettling next to the natives of the planet Bellus. Clement is responsible for those lives and the lives of the natives, Trinity's children, and for building a better future for them all. But when his migrant fleet arrives in the Trinity system, they are faced with enemies both old and new. Former Fleet Admiral Elara DeVore has escaped her exile on the planet Alphus and has vanished into parts unknown. Soon, however, Clement discovers she has a new fleet and a new ally, the Solar League from Earth. The Solar League has arrived with a massive fleet and plans on taking Trinity for itself, then forcing the 5 Suns to surrender. With just a small military fleet to accompany the migrants, Clement is faced with the almost impossible task of defending both his people and the natives from becoming slaves of the Solar League"--